2017
DOI: 10.1016/j.bmc.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and cytotoxicity of Leucetta alkaloids

Abstract: The total synthesis of a number of representative natural products isolated from Leucetta and Clathrina sponges containing a polysubstituted 2-aminoimidazole are described. These syntheses take advantage of the site specific metallation reactions of 4,5-diiodoimidazoles resulting in the syntheses of three different classes of Leucetta derived natural products. The cytotoxicities of these natural products, along with several precursors in MCF7 cells were determined through an MTT growth assay. For comparative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Similarly, the signs of the specic rotation for natural hyrtioreticulins C and D have been reversed following their synthesis, 501 while the structure of topsentin C has also been revised to 1216 some 37 years aer its initial report. 502 A large number of indole-containing alkaloids have been synthesised including makaluvamine O and batzelline D, 503 dictyodendrin G, 504 leucettamine C, 505 isonaamidine E, 506 and cylindradine B, 507 while both enantiomers of the bromotyrosine itampolin A have been produced. 508 Smenospongine A, 509 smenoqualone, 509,510 dehydrocyclospongiaquinone-1, 511 haterumadienone (done in a protecting group-free manner), 512 cheloviolenes A, B and dendrillolide C, 513 astakolactin (revised to 1217), 514 phorbaketal A, 515,516 alotaketals B, C and D, 516 and ansellones A, B and phorbadione 517 are all terpenoids that had syntheses published in 2017.…”
Section: Spongesmentioning
confidence: 99%
“…Similarly, the signs of the specic rotation for natural hyrtioreticulins C and D have been reversed following their synthesis, 501 while the structure of topsentin C has also been revised to 1216 some 37 years aer its initial report. 502 A large number of indole-containing alkaloids have been synthesised including makaluvamine O and batzelline D, 503 dictyodendrin G, 504 leucettamine C, 505 isonaamidine E, 506 and cylindradine B, 507 while both enantiomers of the bromotyrosine itampolin A have been produced. 508 Smenospongine A, 509 smenoqualone, 509,510 dehydrocyclospongiaquinone-1, 511 haterumadienone (done in a protecting group-free manner), 512 cheloviolenes A, B and dendrillolide C, 513 astakolactin (revised to 1217), 514 phorbaketal A, 515,516 alotaketals B, C and D, 516 and ansellones A, B and phorbadione 517 are all terpenoids that had syntheses published in 2017.…”
Section: Spongesmentioning
confidence: 99%
“…Additionally the biological assays of activity were carried out in a successful way. 7 A particular and well-identied synthetic challenge in the total synthesis of keliiquinone is the regioselective N-methylation at the rst position nitrogen of the imidazolone ring (see Fig. 1 Representative imidazole alkaloids isolated from the Leucetta sp.…”
Section: Introductionmentioning
confidence: 99%
“…Since the isolation of NA, numerous studies have described the cytotoxicity of related Leucetta alkaloids against cancer cells, but have failed to discern the relative toxicity between transformed and untransformed cell lines. [4][5][6] We were intrigued that NA and related natural products had been isolated as Zn 2+ dimers from the marine environment (e.g. 2:1 Zn:naamidine A) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…JC-1 staining showed that NA causes mitochondrial membrane depolarization and this was correlated with the induction of apoptosis, providing an alternative explanation for the cytotoxicity of NA in A-431 cells. Since the isolation of NA, numerous studies have described the cytotoxicity of related Leucetta alkaloids against cancer cells, but have failed to discern the relative toxicity between transformed and untransformed cell lines. …”
Section: Introductionmentioning
confidence: 99%